2018
DOI: 10.2147/ccide.s161164
|View full text |Cite
|
Sign up to set email alerts
|

Association of sella turcica bridging with palatal canine impaction in skeletal Class I and Class II

Abstract: PurposeBased on the evidence of the embryonic origin of the sella turcica and the teeth, this retrospective study evaluated the association between sella turcica bridging and palatal canine impaction in skeletal Class I and Class II orthodontic patients.MethodsSixty-two orthodontic patients with palatally impacted canines and 54 controls with erupted canines (aged 12–25 years) were classified into skeletal Class I and Class II (according to ANB angle and Wits analysis). The length, depth, and diameter of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…In another study, Leonardi et al [ 28 ] stated that a sella turcica bridge is more frequent in subjects with dental transposition than in the control group. Similar results have been reported by other authors who investigated correlations between sella turcica bridging and dental abnormalities using lateral and panoramic radiographs [ 21 , 23 , 24 , 25 , 26 , 27 , 29 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In another study, Leonardi et al [ 28 ] stated that a sella turcica bridge is more frequent in subjects with dental transposition than in the control group. Similar results have been reported by other authors who investigated correlations between sella turcica bridging and dental abnormalities using lateral and panoramic radiographs [ 21 , 23 , 24 , 25 , 26 , 27 , 29 ].…”
Section: Resultssupporting
confidence: 90%
“…Concerning dental abnormalities, the authors of the studies included analyzed the following: palatally displaced canines [ 21 , 22 , 27 ], impaction or transposition of canines or premolars [ 23 ], congenitally missing lateral incisors [ 24 ], impacted canines and hyperdontia [ 25 ], impacted canines [ 26 ], dental agenesis [ 26 , 29 ], hyperdontia [ 26 ], maxillary or mandibular dental transposition [ 28 ], congenitally missing second mandibular premolars or the presence of palatally displaced canines [ 30 ]. Thus, in most studies, the study groups were non-homogenous.…”
Section: Resultsmentioning
confidence: 99%
“…Quite a several studies have been provided that certain pathological conditions, such as William syndrome [ 3 ], primary hypopituitarism [ 4 ], growth hormone deficiency [ 5 ], congenital lumbosacral abnormality, and seckel pear syndrome [ 6 ], could alter the shape and size of ST. One of the most popular forms of ST alteration is the fusion of the anterior and posterior clinoid processes, that known as ST bridging [ 1 ]. This form can also be highly related to severe craniofacial deviation, tooth agenesis [ 7 ], canine impaction [ 8 ], and individuals with cleft palate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…found larger values in all three measured parameters in cleft group, only length showed highly significant disparities, however, the type of cleft was not mentioned. In another study, data of 62 subjects with palatally impacted canine revealed significant disparities in ST bridging and three parameters of ST morphology as compared to the control in Saudi population ( Baidas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…and three parameters of ST morphology as compared to the control in Saudi population (Baidas et al, 2018). Studies in the past have shown that patients with disorders or syndromes such as holoprosencephaly (Kjaer et al, 2002), Down syndrome (Hasan et al, 2019), spina bifida (Kjaer et al, 1999), CLP (Alkofide, 2008;Yasa et al, 2017), fragile X syndrome (Kjaer et al, 2001), Williams syndrome (Axelsson et al, 2004), and severe craniofacial deformities (Becktor et al, 2000) have craniofacial malformations which affect the size and/or morphology of ST.…”
mentioning
confidence: 99%